A systematic comparison of biogas development and related policies between China and Europe and corresponding insights. (January 2020) - Xue, Shengrong; Song, Jinghui; Wang, Xiaojiao; Shang, Zezhou; Sheng, Chenjing; Li, Chongyuan; Zhu, Yufan; Liu, Jingyu
Abstract: In order to promote China's biogas industry development, this paper comprehensively compared the biogas status and related policies between China and Europe and tried to find the shortage and potential implications. China has access to abundant biomass resources, with considerable biogas potential and an annual theoretical output of 73.6 billion m 3 . Household-based biogas digesters coexist with medium and large-scale biogas plants (MLBPs) in China. Although the number of MLBPs in China was almost two times higher than Europe, the annul biogas production yield was only half of those in Europe. In China, biogas is mainly used for heating and cooking, and its power generation capacity is far lower than that in Europe. Overall, biogas industry is more commercialized in Europe than China. In terms of biogas related policies, China has an advantage in quantity, but is weak in their implementation. Biogas related policies in China mainly focus on agricultural and rural development, while in Europe, they are aimed at increasing the utilization of renewable energy and reducing greenhouse gas emissions. In addition, policies in China are mostly filled with encouragement, lacking detailed subsidy schemes and modes, whereas in European countries are more targeted and scientific. Based on the dissimilarity of current status and the disparity in policies, a series of countermeasures and suggestions for the development of the Chinese biogas industry are presented. Highlights: China's biomass sources have lower utilization rate compared to Europe. Biogas industry in Europe is more industrialized and commercialized than in China. The related-biogas policy framework of Europe is more mature and perfect. European biogas policy provide valuable reference for China's biogas development. China's biogas industry has great potential for development.